2021
DOI: 10.1039/d0fo02051f
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antioxidant supplementation on skeletal muscle and metabolic profile in aging mice

Abstract: Chronic antioxidant (piceatannol or enzymatically modified isoquercitrin) supplementation improved metabolic profile and locomotor activity in aging mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…These findings are highly relevant for elderly and frail individuals or people who often experience inflammation and loss of muscle quality. Additionally, studies have confirmed that an increase in the intake of components with antioxidant and anti-inflammatory properties from diet or from supplementation could effectively prevent the negative impact of antioxidant deficiency, including oxidative status, lower muscle strength and muscle fatigue after an exercise challenge [ 14 , 21 , 45 , 46 , 47 ]. As typical bioactive peptides, WOPs have been shown to have great anti-inflammatory and antioxidative biological activities [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are highly relevant for elderly and frail individuals or people who often experience inflammation and loss of muscle quality. Additionally, studies have confirmed that an increase in the intake of components with antioxidant and anti-inflammatory properties from diet or from supplementation could effectively prevent the negative impact of antioxidant deficiency, including oxidative status, lower muscle strength and muscle fatigue after an exercise challenge [ 14 , 21 , 45 , 46 , 47 ]. As typical bioactive peptides, WOPs have been shown to have great anti-inflammatory and antioxidative biological activities [ 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sarcopenic patients are susceptible to loss of strength due to muscle fibre loss caused by overproduction of reactive oxygen species and pro-inflammatory mediators, immune senescence, and anabolic resistance status [ 64 , 65 , 66 , 67 ]. The main treatments for sarcopenia are nutritional therapies aimed at achieving a caloric intake of 24–36 kcal/kg body weight/day and a protein intake of 1.0–1.5 g/kg body weight/day [ 68 , 69 ] and supplementation with antioxidants [ 70 ], protein and essential amino acids (EAA) [ 71 ], omega-3 fatty acids, and creatine monohydrate [ 72 ].…”
Section: Musclesmentioning
confidence: 99%
“…As muscle is a critical organ in regulating the metabolism of the whole body, a metabolic profile under sitting and exercise conditions was also determined. Chronic administration of EMIQ prevented the age-related decrease in lipid oxidation and slightly improved the antioxidant capacity and oxidative stress in skeletal muscle, increasing the expression of genes for the antioxidant enzyme glutathione peroxidase and reducing the level of carbonyl proteins [ 66 ].…”
Section: Bioactivitymentioning
confidence: 99%